Circulating IL-17F, but not IL-17A, is elevated in severe COVID-19 and leads to an ERK1/2 and p38 MAPK-dependent increase in ICAM-1 cell surface expression and neutrophil adhesion on endothelial cells - Bédard-Matteau, Jérôme; Soulé, Antoine; Liu, Katelyn Yixiu; Fourcade, Lyvia; Fraser, Douglas D.; Emad, Amin; Rousseau, Simon (Frontiers in Immunology, 2024)
Severe COVID-19 is associated with neutrophilic inflammation and immunothrombosis. Several members of the IL-17 cytokine family have been associated with neutrophilic inflammation and activation of the endothelium. Therefore, we investigated whether these cytokines were associated with COVID-19 in participants to the Biobanque québécoise de la COVID-19 (BQC19), a prospective observational cohort designed to support investigations on COVID-19. We found increased IL-17D and IL-17F plasma levels when comparing SARS-CoV-2-positive + vs -hospitalized participants. Moreover, increased plasma levels of IL-17D, IL-17E and IL-17F were noted when comparing severe versus mild COVID-19. We validated in an independent cohort from the Western University (London, Ontario) that IL-17F, but not IL-17A, was significantly elevated in people with COVID-19 compared to healthy controls and with more severe disease. In vitro work on endothelial cells treated with 100 ng/ml of IL-17F for 24 hours showed an increase of intercellular adhesion molecule 1 (ICAM-1) at the surface level accompanied by neutrophil adhesion. The introduction of two inhibitors of the MAPK family, PD184352 (an MKK1/MKK2 inhibitor) and BIRB0796 (a p38 MAPK inhibitor), significantly reduced the binding of neutrophils while also reducing ICAM-1 expression at the surface level of endothelial cells, but not its intracellular expression. Overall, these results have identified an association between two cytokines of the IL-17 family (IL-17D and IL-17F) with COVID-19 and disease severity. Considering that IL-17F stimulation promotes neutrophil adhesion to the endothelium in a MAPK-dependent manner, it is attractive to speculate that this pathway may contribute to pathogenic immunothrombosis in concert with other molecular effectors.